2022
DOI: 10.1002/advs.202203927
|View full text |Cite
|
Sign up to set email alerts
|

ε‐Ga2O3: An Emerging Wide Bandgap Piezoelectric Semiconductor for Application in Radio Frequency Resonators

Abstract: The explosion of mobile data from the internet of things (IoT) is leading to the emergence of 5G technology with dramatic frequency band expansion and efficient band allocations. Along with this, the demand for high-performance filters for 5G radio frequency (RF) front-ends keeps growing. The most popular 5G filters are constructed by piezoelectric resonators based on AlN semiconductor. However, AlN possesses a piezoelectric constant d 33 lower than 5 pm V −1 and it becomes necessary to develop novel semicondu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…In our earlier work [ 30 ], we reported the experimental observation of a 2DHG at the heterointerface of κ-Ga 2 O 3 films with basal plane (0001) AlN on Si(111). It has also been suggested that the considerable piezo-electric polarization of κ-Ga 2 O 3 could be employed in RF resonators and modulators [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier work [ 30 ], we reported the experimental observation of a 2DHG at the heterointerface of κ-Ga 2 O 3 films with basal plane (0001) AlN on Si(111). It has also been suggested that the considerable piezo-electric polarization of κ-Ga 2 O 3 could be employed in RF resonators and modulators [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ga 2 O 3 is thus considered a new-generation semiconductor that meets the power demands of semiconductor devices and integrated technologies towards higher energy efficiency, higher voltage-resistance and higher frequency. 5,6 Meanwhile, Ga 2 O 3 exhibits numerous potential applications in terms of high-power semiconductor devices, light-emitting diode chips, and various sensor components. 7,8 As advanced packaging technologies, multi-chip modules (MCM) and a system-in-a-package (SiP) can provide excellent "More-Than-Moore" solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to third-generation semiconductors, such as GaN and SiC, β-Ga 2 O 3 possesses several advantages, including a wider bandgap, a higher breakdown field strength, and the ability to easily grow high-quality single crystals in large sizes. As a result, β-Ga 2 O 3 -based photodetectors have demonstrated exceptional sensitivity and responsivity in the deep-ultraviolet (DUV) range, making them ideal for DUV sensing and imaging applications . Moreover, β-Ga 2 O 3 -based transistors have exhibited remarkable electron mobility, which makes them highly suitable for high-frequency and high-power electronic applications. However, during the growth process, Ga 2 O 3 inevitably introduces oxygen vacancies, which pose significant challenges to intrinsic carrier regulation, p-type doping, and the formation of stable Schottky contacts. , For instance, the presence of oxygen vacancies leads to persistent photoconductivity (PPC) effects, resulting in unexpected photoconductive gains but slow response speed due to trapping effects. Furthermore, the oxygen vacancy defects (V O ) on the surface of Ga 2 O 3 cause electrons to be transported through tunneling puncture effects that result in the high reverse leakage current of transistors. …”
mentioning
confidence: 99%